Improving Business Performance Through Creativity, Innovation and Digital Transformation of Micro, Small and Medium Enterprises: Mediated by Competitive Advantage - Juharsah, Juharsah; Anto, La Ode; Hadisantoso, Erwin; Putera, Asrip; Mahrani, Sri Wiyati; Hamid, Wahyuniati; Saguinsin, Israel DC; Magdaraog Jr, Gualberto; Hudtohan , Emiliano T.; Gabriel S , Castilia Zeal; Syahrun , Diyyanah Nur Fathyyah (International Journal of Management and Education in Human Development, 2024)
The purpose of this study is to examine and analyze the Influence of Creativity, Innovation, and Digital Transformation on Business Performance of Micro, Small, and Medium Enterprises: Mediated by Competitive Advantage (Study on Culinary Business in Malolos City Philippines). The population in this study was MSMEs owners engaged in the Culinary Business for at least 3 years in Malolos City, Bulacan Philippines, as many as 101 MSME owners, The sample consideration in this study was that respondents had a minimum education level of high school because they were considered capable of making good financial decisions. While for the business criteria, the researcher decided on the minimum criteria for the business to have been running for 3 years and have a minimum turnover of PHP 15,000 per month, the number of samples determined in this study was 101 respondents. The data analysis technique used was Smart Partial least square (SmartPLS). The results of the study indicate that Creativity has a significant influence on Business Performance of MSMEs in Malolos City Philippines. Creativity has a significant effect on the Competitive Advantage of MSMEs in Malolos City Philippines. Innovation has a significant effect on the Competitive Advantage of MSMEs in Malolos City Philippines. The relationship between innovation and Business performance in the study is directly proportional where it can be said that the better the innovation, the better the business performance and provide a significant impact. Innovation has a significant effect on Business Performance of MSMEs in Malolos City Philippines. The relationship between Innovation and competitive advantage in the study is directly proportional where it can be said that the better the creativity is carried out, the better the competitive advantage have a significant effect. Digital Transformation has a significant effect on Business Performance of MSMEs in Malolos City Philippines. The relationship between digital transformation and business performance in the study is directly proportional where it can be said that the better the digital transformation, the better the business performance Personnel and have a significant impact. Digital Transformation Have a Significant Influence on the Competitive Advantage of MSMEs in Malolos City Philippines. The relationship between digital transformation and competitive advantage in the study is directly proportional where it can be said that the better the digital transformation, the better the competitive advantage will be and have a significant impact. Competitive Advantage has a significant effect on Business Performance of MSMEs in Malolos City Philippines. Competitive Advantage acts as a mediator influence Creativity towards Business Performance of MSMEs in Malolos City Philippines. Thus, it can be said that competitive advantage is able to mediate the influence of the creativity on performance. Competitive Advantage acts as mediation influence Innovation to Business Performance of MSMEs in Malolos City Philippines.